Kinetics and thermodynamics of thermal degradation and antimicrobial activity of zinc phenothiazine oleate complex (Bulletin of Pure and Applied Sciences-Chemistry, 2020)
The role of metals in organic synthesis has been  well known from the beginning of the  development of synthetic procedure in organic  Chemistry. Heterocyclic complexes have  attracted increasing interest because of their role  in the understanding of molecular process  occurring in biochemistry and coordination  chemistry. The Nitrogen donor aromatic ligand  constitutes an important and interesting class of  drugs / dyes not only for synthetic investigation  but also for their usefulness to resist diseases.  Colloidal systems are extremely wide spread in  nature and are of great practical importance in  our daily life. Surfactants are very useful in  modern engineering and pharmaceuticals due to  formation of micelles in solutions and high  surface activity. Present work has been initiated  with a view to obtain a profile as to the nature  and structure of complex of phenothiazine with  zinc oleate in different non-aqueous solvents that  are of great significance in explaining their  characteristics under different conditions. The  present work reveals synthesis of zinc soap and  its complex with phenothiazine ligand. For this  synthesis the para substituted aniline was  selected as the most suitable initial compound. An analytical and spectral study (IR, NMR) of  this complex has been done. In order to know  their thermal stability, thermogravimetric  analysis has been done. A biocidal activity of  complex has been carried to access their  comparative toxicity.
Keywords: Kinetics; thermodynamics; degradation; antimicrobial; phenothiazine